2021
DOI: 10.1093/ehjdh/ztab043
|View full text |Cite
|
Sign up to set email alerts
|

The 12-lead electrocardiogram as a biomarker of biological age

Abstract: Background We have demonstrated that a neural network is able to predict a person’s age from the electrocardiogram (ECG) [artificial intelligence (AI) ECG age]. However, some discrepancies were observed between ECG-derived and chronological ages. We assessed whether the difference between AI ECG and chronological age (Age-Gap) represents biological ageing and predicts long-term outcomes. Methods and results We previously deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 32 publications
4
61
0
1
Order By: Relevance
“…Furthermore, they investigated the residual between ECG-age and chronological age and found the residual is an independent predictor of all-cause Abbreviations: CVD, cardiovascular disease; ECG, Electrocardiography; DLM, deep learning model; AMI, acute myocardial infarction; CAD, coronary artery disease; CHF, congestive heart failure; AF, atrial fibrillation; DM, diabetes mellitus; HTN, hypertension; CKD, chronic kidney disease; AI, artificial intelligence; SCORE, Systematic COronary Risk Evaluation; ECG-age, ECG-based heart age; BMI, body mass index; HR, hazard ratio; CI, conference interval; ROC, receiver operating characteristic; AUC, area under curve; eGFR, estimated glomerular filtration rate; TG, triglycerides; COPD, chronic obstructive pulmonary disease; K, potassium; Na, sodium; Cl, chloride; Ca, calcium; Alb, albumin; GLU, glucose; HbA1c, glycated hemoglobin; BUN, blood urea nitrogen; Cr, creatinine; WBC, white blood cell count; PLT, platelet; Hb, hemoglobin; AST, aspartate aminotransferase; ALT, alanine aminotransferase; TG, triglyceride; TC, total cholesterol; LDL, low-density lipoprotein cholesterol; HDL, high-density lipoprotein cholesterol. mortality and cardiovascular mortality (23). Currently, many research teams had pointed out the strength of mortality risk stratification using ECG-age (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they investigated the residual between ECG-age and chronological age and found the residual is an independent predictor of all-cause Abbreviations: CVD, cardiovascular disease; ECG, Electrocardiography; DLM, deep learning model; AMI, acute myocardial infarction; CAD, coronary artery disease; CHF, congestive heart failure; AF, atrial fibrillation; DM, diabetes mellitus; HTN, hypertension; CKD, chronic kidney disease; AI, artificial intelligence; SCORE, Systematic COronary Risk Evaluation; ECG-age, ECG-based heart age; BMI, body mass index; HR, hazard ratio; CI, conference interval; ROC, receiver operating characteristic; AUC, area under curve; eGFR, estimated glomerular filtration rate; TG, triglycerides; COPD, chronic obstructive pulmonary disease; K, potassium; Na, sodium; Cl, chloride; Ca, calcium; Alb, albumin; GLU, glucose; HbA1c, glycated hemoglobin; BUN, blood urea nitrogen; Cr, creatinine; WBC, white blood cell count; PLT, platelet; Hb, hemoglobin; AST, aspartate aminotransferase; ALT, alanine aminotransferase; TG, triglyceride; TC, total cholesterol; LDL, low-density lipoprotein cholesterol; HDL, high-density lipoprotein cholesterol. mortality and cardiovascular mortality (23). Currently, many research teams had pointed out the strength of mortality risk stratification using ECG-age (24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study used 774,783 patients to train a DLM for predicting the age of the patient, which confirmed the feasibility of age extraction from ECG ( 22 ). Furthermore, they investigated the residual between ECG-age and chronological age and found the residual is an independent predictor of all-cause mortality and cardiovascular mortality ( 23 ). Currently, many research teams had pointed out the strength of mortality risk stratification using ECG-age ( 24 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attia, et al, showed that by using a deep neural network (DNN) artificial intelligence (AI) technique, a patient’s chronological age could be predicted, and that if the difference between the predicted and actual age was small, prognosis was good 8 . When Heart Age by Attia et al’s technique was older than the chronological age, the risk of future death was increased 7 . This corresponds well to the findings in our study that ECG Heart Age increased with increasing burden of cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…If standard 10-second ECG recordings could be used instead, the clinical impact might be enhanced. Moreover, artificial intelligence has been used to estimate ECG Heart Age using the 10-second resting 12-lead ECG 7,8,10 . However, artificial intelligence techniques are limited by their “black box” approach, whereby the clinician does not have transparency as to the exact source(s) of the changes in the ECG that can affect an ECG Heart Age or other output 18,19 .Therefore, the aim of the study was to predict 5-minute ECG Heart Age from measures available by 10-second 12-lead ECG, and to compare the 10-second ECG Heart Age to chronological age in healthy subjects, subjects with cardiovascular risk factors, and patients with established cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ventricular fibrillation is predominantly observed in the aged (Iwami et al, 2003). Recent studies have shown that the difference between the chronological age and DNN-estimated age can be used as a predictor of mortality (Ladejobi et al, 2021;Lima et al, 2021).…”
Section: Demographic Featuresmentioning
confidence: 99%